Fairness and Contract Design - Ernst Fehr; Alexander Klein; Klaus M. Schmidt (Sonderforschungsbereich/Transregio 15 - Governance and the Efficiency of Economic Systems (GESY), 2005)
We show experimentally that fairness concerns may have a decisive impact on the actual and optimal choice of contracts in a moral hazard context. Bonus contracts that offer a voluntary and unenforceable bonus for satisfactory performance provide powerful incentives and are superior to explicit incentive contracts when there are some fair-minded players. But trust contracts that pay a generous wage upfront are less efficient than incentive contracts. The principals understand this and predominantly choose the bonus contracts. Our results are consistent with recently developed theories of fairness, which offer important new insights into the interaction of contract choices, fairness and incentives.
urn:nbn:de:bvb:19-epub-13483-1
Keywords: C7; C9; J3; 330; Moral Hazard; Incentives; Bonus Contract; Trust Contract; Fairness; Inequity Aversion